CLASSIFICATIONS OF INTERACTING ORGANIZATIONS - G. Avetisayn; A. Raichenko (Вестник университета, 2017)
In article the social and economic organizations and their segregation are considered. For the purpose of structurization of the social and economic organizations classifications of the interacting organizations in fact are defined, to forms and types and also creation of article on examples of the energy sector in general, and economies of member countries of the Eurasian Economic Union is caused. Arguments in favor of the prospects of development of the energy sector of the Eurasian Economic Union are adduced, author's views of the further future of economies of the considered countries are given.